The Affectivity in Classroom Climate of Students of Basic General Education - Gladis Mercedes Mendoza Suarez, Maria Elena Martinez Moya (International Journal of Advanced Science and Technology, 2020)
Currently, affectivity is considered a primary requirement in the integral development of children and in the teaching-learning process, depending on the classroom climate or the interpersonal relationships that it establishes in the surrounding environment. This research aims to describe the importance of affectivity in the classroom climate of students of Basic General Education. The structure of this research begins with a brief introduction that describes the reality of affectivity in the classroom climate of students at the level of Latin America, Ecuador and Manabí, emphasizing the negative consequences that occur in the absence of this factor in the different educational centers. Then the methodological process is described, followed by an analysis and discussion of affectivity, classroom climate, school coexistence, the factors that influence it and a table of investigations. The inductive method was used because it started from the general to the particular, which allowed analyzing the problems at the macro, meso and micro levels with a descriptive qualitative approach. The results obtained are based on the analysis and interpretation of the bibliographic review by different authors.